Revisión documental sobre didácticas de la enseñanza del inglés como lengua extranjera para población en situación de discapacidad auditiva en contextos de inclusión educativa (2021)
This compilation monograph proposes a documentary review that aims to identify the didactics regarding the teaching and learning processes of English as a foreign language in a population with hearing disabilities in a situation of school inclusion. To this end, from an interpretive research perspective, in this case the state of the art, an exercise of four moments is proposed that were established as follows: first, the selection of some study units; in the second instance, the information organization was carried out by means of two data collection instruments (bibliographic matrix and RAE); In a third moment, the data processing was carried out, yielding four categories of analysis, which are: foreign language teaching practices in the population with hearing disabilities, adaptation of the curriculum, learning environments and language evaluation processes English foreigner, which must be carried out with this particular population; and finally the conclusions